2013
DOI: 10.3348/kjr.2013.14.5.733
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic-Guided Radiofrequency Ablation of Recurrent or Residual Hepatocellular Carcinomas around Retained Iodized Oil after Transarterial Chemoembolization

Abstract: ObjectiveTo assess the clinical efficacy, safety, and risk factors influencing local tumor progression, following CT-guided radiofrequency ablation (RFA) of recurrent or residual hepatocellular carcinoma (HCC), around iodized oil retention.Materials and MethodsSixty-four patients (M : F = 51 : 13, 65.0 ± 8.2 years old) with recurrent or residual HCC (75 index tumors, size = 14.0 ± 4.6 mm) had been treated by CT-guided RFA, using retained iodized oil as markers for targeting. The technical success, technique ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Koh et al evaluated the efficacy of CT-guided RFA for recurrent or residual HCC around the retained iodized oil after TACE in 64 patients with 75 viable HCCs. The authors reported 1-and 2-year LTP rates of 17.5% and 37.5%, respectively [30], which was higher than the 13.8% and 20.6% LTP rate after TAE combined with RFA in our study. This result appears to be attributed to the important role of preoperative planning in 3DVAPS.…”
Section: Discussioncontrasting
confidence: 83%
“…Koh et al evaluated the efficacy of CT-guided RFA for recurrent or residual HCC around the retained iodized oil after TACE in 64 patients with 75 viable HCCs. The authors reported 1-and 2-year LTP rates of 17.5% and 37.5%, respectively [30], which was higher than the 13.8% and 20.6% LTP rate after TAE combined with RFA in our study. This result appears to be attributed to the important role of preoperative planning in 3DVAPS.…”
Section: Discussioncontrasting
confidence: 83%
“…The difference between the survival benefits of these two therapeutic modalities remains unclear. Moreover, with the merit of high resolution and without interference of gas released during the procedure, the use of CT guidance in the RFA procedure helps operators to ablate even large tumors with a safety margin greater than that with the widely used ultrasonographic guidance 6 , 13 . The aim of this work was to compare the safety and efficacy of TACE in combination with available CT-guided RFA with that of SR in patients with HCC who met the up-to-seven criteria in a large multicenter case-matched study.…”
Section: Introductionmentioning
confidence: 99%
“…However, a combination of ultrasound guidance, a volume navigation system with fusion of ultrasound/CT or ultrasound/MRI images, and C-arm CBCT has not been reported. In conventional CT-guided RFA, pneumothorax was noted in 9 out of 71 patients (12.7%) [38], which compares poorly with the corresponding 3 out of 198 cases (1.5%) in this study. As we described, the electrode was first inserted into the target lesion under ultrasound guidance - or by using the volume navigation system with fusion images, if necessary.…”
Section: Discussionmentioning
confidence: 45%
“…In previous reports, electrode insertion was guided by C-arm CBCT with integrated navigation software [19,20] or standard CT alone [35,36,37,38]. However, a combination of ultrasound guidance, a volume navigation system with fusion of ultrasound/CT or ultrasound/MRI images, and C-arm CBCT has not been reported.…”
Section: Discussionmentioning
confidence: 99%